A major practicum report at Euro Swiss Food Inc., Yakal St. San Antonio Village, Makati City - Cotejo, Regina Tart Mariano (2007)
A practicum of 288 hours was conducted last April 19 to May 23, 2007. It covered the major plant operations particularly on production line: from the acquisition of raw materials, processing, until dispatch of the finished products to the market. After the practicum, the student was able to gather important information about the company's profile, company's major operations, and their good manufacturing and processing standards implementation. The student was also able to relate in the practicum the knowledge acquired from the academe as a Food Technologist and formulate a technical analysis focusing on the production line of the company. Some problems related to food processing were also noted and provided with recommendations for the improvement of the company's operation.
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2007
Keywords: Meat products; Euro Swiss Food Inc